Studies on Dielectric Behaviour of Some Long Chain Alcohols and Their Mixtures With a Non-Polar Solvent at Various Concentrations (Biological Sciences - PJSIR, 2006)
. Dielectric constant, refractive index and the Kirkwood linear correlation factor of 1-propanol, 1-butanol and 1-pentanol in mixtures with carbon tetrachloride at various concentrations have been measured at fixed frequency (100 KHz) at 303.15 K. For the study of dielectric properties of polar molecules in a non-polar solvent at different concentrations, polarization per unit volume and excess free-energy of mixing were evaluated at this temperature. In order to study the association of polar molecules in such a non-polar solvent, the Kirkwood correlation factor (g) between molecular pairs, which exists due to the hydrogen bond association suggesting the presence of some dimen- sions in the liquid phase with a number of dimmers, was determined. The refractive index and dielectric constant measurements are expected to shed some light on the configuration of molecules in various mixtures, and give some idea about the specific interactions between components, which decrease with the increase in the concentrations of alcohol. All the three mixtures showed different behaviour for the value of correlation factor (g) as a function of concentration. The response of 1-pentanol was broadly identical to that of small chain alcohols. The different behaviour of the correlation factor (g) was interpreted in terms of the Kirkwood-Frohlich theory, as it takes into account, explic- itly, such types of short and long range interactions of a mixture of polar molecules with non-polar solvents.